Dentigerous cyst of maxilla and mandible associated with ectopic teeth- a case report - Singh, Geeta; Bhutia, Dichen Palmo; Singh, Diksha; Gamit, Jagdish; Vignesh, U (International Journal of Dental Research, 2017)
Background: Dentigerous cyst (DC) is the second most common cyst of the jaw after radicular, affecting mostly the permanent dentition in the mandible (70%). DC Of maxillary sinus involving ectopic teeth is rare.Case details: We report a case of DC of maxillary sinus as well as anterior mandible associated with ectopic teeth, in a non-syndromic 8 years old boy who underwent cyst enucleation along with extraction of the involved teeth.Conclusion: DC affecting both maxilla and mandible is a less common entity. Treatment modality can range from enucleation to simple marsupilisation depending upon the extent of the lesion.